Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Keuangan - Rangga Friday Syah Pratama; Rinwantin (Jurnal Akuntansi dan Audit Syariah)
Banking is one of the financial institutions that has activities to collect funds from the public in the form of savings and distribute them to the public in the form of credit and/or other forms. The purpose of banking is to make a profit. The level of a bank's ability to make a profit is measured by Return on Assets (ROA). The purpose of this study is to test the effect of the Capital Adequacy Ratio (CAR), Operating Costs Operating Income (BOPO), and Loan to Deposit Ratio (LDR), on the Return on Assets (ROA) of state-owned banks listed on the Indonesia Stock Exchange during 2019-2023. The samples used in this study were those consistently listed on the Indonesia Stock Exchange during the 2019-2023 period. This study uses a purposive sampling method to determine the sample, resulting in 4 companies and 80 quarterly samples. Data were analyzed using multiple linear regression methods and descriptive statistics. The results of this study found that CAR has a positive and significant effect on ROA with a calculated f value of 316.135> f table 2.73 with a significant value of 0.000 <0.05. BOPO has a negative and significant effect on ROA with a calculated f value of 316.135> f table 2.73 and a significant value of 0.000 <0.05. and LDR has a positive and insignificant effect on ROA with a calculated t of 1.786> t table 1.665 and a significant value of 0.078> 0.05. In addition, this study also proves that CAR, BOPO, LDR have a simultaneous effect on ROA of state-owned banks. The coefficient of determination (Adjusted R2) of the regression model is 92.3%. This means that the independent variables can explain ROA by 92.3%, the remaining 7.7% is explained by other variables not analyzed in this study.